О поедании рептилий птицами Краснодарского края - Пекло, А.М.; Очаповский, В.С. (Вестник зоологии, 1976)
The authors studied 6500 stomaches, guano and food remains for 195 species of birds from 19 orders inhabiting the Krasnodar territory. Reptiles were found in food of 24 species. Percentage of reptile occurrence in food of the total amount of the studied samples was calculated for most birds.